Peningkatan Keterampilan Mendeskripsikan Benda Secara Tertulis pada Pembelajaran Tematik Muatan Bahasa Indonesia dengan Menggunakan Model Kooperatif Tipe Make A Match di Kelas II SDN 092/X Kampung Laut Semester Ganjil Tahun Ajaran 2021/2022 - Siti Purwaningsih (Departement of Mathematics Education, 2022)
This study aims to describe and obtain information on improving Indonesian language learning outcomes through the Make A Match Cooperative Model. This research is a classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this research were 3rd grade students of SDN 092/X Kampung Laut. This research was conducted in the even semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that the use of the Make A Match Cooperative Model could improve the Indonesian language learning outcomes for second grade students at SDN 092/X Kampung Laut.